"Estudio del distanciamiento de siembra y altura del sistema de sostenimiento sobre la producción y calidad de la maracura (Passiflora edulis, var. Flavicarpa Degener)". - Fuentes vera, Johanna Elizabeth (2015)
The present investigation was carried out, in the Experimental Station - Tropical Pichilingue of the INIAP, located in the Km 5 of the road Quevedo - The Connection, in the canton Quevedo, county of The Ríos. The maracuyá variety INIAP was used 2009 that it comes from a selection stratified masal carried out in the 2007, of a maracuyá population introduced from EMBRAPA (Brazil). The selection was carried out by the Program of Fruticultura of the Experimental Station Portoviejo of the INIAP, during the years 2008 - 2009. It was selected individual plants, taking into account the productivity, size and weight of the fruits that are characters of the heredabilidad. The studied objectives were, to study the siembra distancing and maintenance height in maracuyá; to select the best distancing and maintenance system that adapt to the climatic conditions of the area and to carry out the economic analysis of the treatments in study.